Liver and Mesenteric Hydatid Cyst in a Child—A Brief Report with Review of Literature - Vutukuru, Sravanthi; Peters, Nitin James; Mewara, Abhishek; Kaur, Simran; Samujh, Ram (Journal of Laboratory Physicians, 2023)
Hydatid disease, though endemic in the sub-Himalayan region of the subcontinent, is relatively rare in the pediatric age group. The simultaneous existence of hydatid in two or more organs is very rare, seen only in 5 to 13% of patients. We report an 11-year-old patient, who presented with painless progressive abdomen distension over 6 months. Imaging studies revealed a large cystic lesion occupying majority of the abdomen. The patient was diagnosed to have a hydatid cyst of the liver and mesentery, with multiple daughter cysts intraoperatively. Excision of the cyst was done and the patient is doing well on postoperative follow-up of 1 year.
Keywords: abdominal cysts; hepatic hydatid; mesenteric hydatid cysts; multiple hydatids